COMPETENCE DOCTORAL - Giudice Baca, Víctor (2015)
Competencies are skills, knowledge, abilities of a university graduate. Competencies may be treated as generic, specific and transversal to several university graduates. Transversal competencies are more demanded to Doctoral Graduates. Peruvian University law 30220 has shortened Master Studies to one year and enlarged Doctoral Studies to three years. (Articles 44.4 and 44.5).This paper exposes the experience to use the third year of Doctoral Studies and send the Doctoral Graduates to Research Centers in Europe or other continents. The paper found 56 doctoral skills.